Influence of energetic particle precipitation on Antarctic stratospheric chlorine and ozone over the 20th century - Ville Maliniemi; Pavle Arsenovic; Annika Seppälä; Hilde Nesse Tyssøy (Zenodo, 2022)
Data used in Maliniemi et al. (2022) Atmos. Chem. Phys. research article. SOCOL3-MPIOM chemistry-climate model simulations with particle precipitation forcing (_exp) and without particle precipitation forcing (_ref). Zonally averaged monthly absolute values during 1899-2008 in latitudes from -90 to 90 and in altitudes from 0.01 to 1000 hPa. Data matrices are 48x30x12x110x11 (Lat x Alt x Month x year x ensemble).